NURSING DYSPHAGIA SCREENING TO PREVENT THE OCCURRENCE OF PNEUMONIA IN STROKE PATIENTS IN INDONESIA: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i1.58 - Siti - Aisah; Agung - Waluyo (Alta Dharma Publisher, 2019)
Abstract Background: Dysphagia is a frequent complication in stroke. Patients with dysphagia have potential risk of pneumonia, malnutrition, dehydration, increased length of stay and even death. One og nursing intervention that is considered important in the management of stroke patients is dysphagia screening because it can reduce aspiration and pneumonia and other complications that can occur in dysphagia. Aim: The aim of this literature review was to comparison between The National Institutes Of Health Stroke Scale, Nursing Admission Screening Tools, and Functional Independence Measure to preventing the occurrence of pneumonia in stroke patients in Indonesia. Design: This paper used narrative review. Data source: A literature search was conducted of articles published from 2010 through October 2018 using the PubMed, Embase, Cochrane Library and Ebscohost databases on compared three of dysphagia screening. Result: This search resulted in a total of 16 articles. Evidence has indicated that The National Institutes Of Health Stroke Scale Screening is considered to be the most effective type of dysphagia screening in preventing pneumonia in stroke patients who experience dysphagia. Conclusion: The NIHSS has a sensitivity value, specificity, positive predictive value, and negative predictive value that is quite good and considered safe to be applied in screening for dysphagia in stroke patients in Indonesia. Keywords: dysphagia screening, dysphagia in stroke, The National Institutes of Health Stroke Scale, Nursing Admission Screening Tools, Functional Independence Measure